591. Adintrevimab (ADI) Population Pharmacokinetics (PPK) in Phase 1 and Phase 2/3 COVID-19 Prevention and Treatment Study Participants. (15th December 2022) - Rubino, Christopher M; Cammarata, Anthony P; Ambrose, Paul; Schmidt, Pete; Popejoy, Myra; Gong, Jean; Pu, Xia
Abstract: Background: ADI is a fully human IgG1 monoclonal antibody engineered to have an extended half-life with high potency and broad neutralization against SARS-CoV-2 and other SARS-like coronaviruses with pandemic potential. Our objective was to develop a PPK model that describes the serum ADI concentration-time profile following intravenous (IV) and intramuscular (IM) administration. Methods: The ADI PPK model was developed on PK data from a Phase 1 single-ascending dose study (24 adults, IV and IM) and from Phase 2/3 COVID-19 prevention (EVADE; 659 adults, IM) and treatment (STAMP; 189 adults, IM) studies. 1, 486 PK samples were included in the analysis. The impact of covariates (e.g. body weight, age, and baseline viral load) on ADI serum disposition were evaluated. Prediction-corrected visual predictive check (PC-VPC) plots were used to qualify the PPK model. Participant-specific ADI exposure estimates were generated using individual post hoc PK parameters. Results: The PPK model is comprised of 2 systemic compartments, zero-order infusion for IV administration and first-order absorption for IM administration and provided a robust fit to the data based on the PC-VPC plots and goodness-of-fit plots (data not shown). Body weight influenced clearance, intercompartmental clearance, and central and peripheral volume compartments. The relationship between body weight and clearance was not suggestive of the need for dose adjustment over the population weight range studied (38.6 to 178.7 kg). There was no apparent impact of baseline viral load or age on ADI clearance. The median [range] half-lives in days by study; Phase 1 (α1.71 [1.18-2.46]; β 125 [117-149]), Phase 2/3 prevention (α 1.86 [0.640-3.13]; β 136 [105-209]), and Phase 2/3 treatment (α 1.89 [0.631-3.01]; β 136 [108-206]). The population mean IM bioavailability estimate was 90.5%. The figure shows the PPK model median (90% confidence interval) concentration-time profile following a single 300 mg IM ADI dose by study. Conclusion: The PPK model provided a precise and unbiased fit to the observed ADI concentration-time data and will be useful for future PK-pharmacodynamic analyses. Moreover, ADI demonstrated high IM bioavailability and a median terminal elimination half-life of 125 to 136 days. Disclosures: Christopher M. Rubino, PharmD, Adagio Therapeutics: Grant/Research Support|Amplyx Pharmaceuticals, Inc: Grant/Research Support|AN2 Therapeutics: Grant/Research Support|Antabio SAS: Grant/Research Support|Arcutis Biotherapeutics, Inc: Grant/Research Support|B. Braun Medical Inc.: Grant/Research Support|Basilea Pharmaceutica: Grant/Research Support|Boston Pharmaceuticals: Grant/Research Support|Bravos Biosciences: Ownership Interest|Celdara Medical LLC: Grant/Research Support|Cidara Therapeutics Inc: Grant/Research Support|Cipla USA: Grant/Research Support|Crestone Inc: Grant/Research Support|CXC: Grant/Research Support|Debiopharm International SA: Grant/Research Support|Entasis Therapeutics: Grant/Research Support|Evopoint Biosciences Co.: Grant/Research Support|Fedora Pharmaceuticals: Grant/Research Support|GlaxoSmithKline: Grant/Research Support|Hoffmann-La Roche: Grant/Research Support|ICPD: Ownership Interest|ICPD Biosciences, LLC.: Ownership Interest|Insmed Inc.: Grant/Research Support|Iterum Therapeutics Limited: Grant/Research Support|Kaizen Bioscience, Co.: Grant/Research Support|KBP Biosciences USA: Grant/Research Support|Lassen Therapeutics: Grant/Research Support|Matinas Biopharma: Grant/Research Support|Meiji Seika Pharma Co., Ltd.: Grant/Research Support|Melinta Therapeutics: Grant/Research Support|Menarini Ricerche S.p.A: Grant/Research Support|Mutabilis: Grant/Research Support|Nabriva Therapeutics AG: Grant/Research Support|Novartis Pharmaceuticals Corp.: Grant/Research Support|Paratek Pharmaceuticals, Inc.: Grant/Research Support|PureTech Health: Grant/Research Support|Sfunga Therapeutics: Grant/Research Support|Spero Therapeutics, : Grant/Research Support|Suzhou Sinovent Pharmaceuticals Co.: Grant/Research Support|TauRx Therapeutics: Grant/Research Support|Tetraphase Pharmaceuticals: Grant/Research Support|tranScrip Partners: Grant/Research Support|Utility Therapeutics: Grant/Research Support|Valanbio Therapeutics, Inc.: Grant/Research Support|VenatoRx: Grant/Research Support|Wockhardt Bio AG: Grant/Research Support Anthony P. Cammarata, M.S., Adagio Therapeutics, Inc.: Grant/Research Support|Amplyx Pharmaceuticals, Inc.: Grant/Research Support|AN2 Therapeutics: Grant/Research Support|Antabio SAS: Grant/Research Support|Arcutis Biotherapeutics, Inc.: Grant/Research Support|B. Braun Medical Inc.: Grant/Research Support|Basilea Pharmaceutica: Grant/Research Support|Boston Pharmaceuticals: Grant/Research Support|Celdara Medical LLC: Grant/Research Support|Cidara Therapeutics Inc.: Grant/Research Support|Cipla USA: Grant/Research Support|Crestone Inc.: Grant/Research Support|CXC: Grant/Research Support|Debiopharm International SA: Grant/Research Support|Entasis Therapeutics: Grant/Research Support|Evopoint Biosciences Co.: Grant/Research Support|Fedora Pharmaceuticals: Grant/Research Support|GlaxoSmithKline: Grant/Research Support|Hoffmann-La Roche: Grant/Research Support|Insmed Inc.: Grant/Research Support|Iterum Therapeutics Limited: Grant/Research Support|Kaizen Bioscience, Co.: Grant/Research Support|KBP Biosciences USA: Grant/Research Support|Lassen Therapeutics: Grant/Research Support|Matinas Biopharma: Grant/Research Support|Meiji Seika Pharma Co., Ltd.: Grant/Research Support|Melinta Therapeutics: Grant/Research Support|Menarini Ricerche S.p.A.: Grant/Research Support|Mutabilis: Grant/Research Support|Nabriva Therapeutics AG: Grant/Research Support|Novartis Pharmaceuticals Corp.: Grant/Research Support|Paratek Pharmaceuticals, Inc.: Grant/Research Support|PureTech Health: Grant/Research Support|Sfunga Therapeutics: Grant/Research Support|Spero Therapeutics: Grant/Research Support|Suzhou Sinovent Pharmaceuticals Co.: Grant/Research Support|TauRx Therapeutics: Grant/Research Support|Tetraphase Pharmaceuticals: Grant/Research Support|tranScrip Partners: Grant/Research Support|Utility Therapeutics: Grant/Research Support|Valanbio Therapeutics, Inc.: Grant/Research Support|VenatoRx: Grant/Research Support|Wockhardt Bio AG: Grant/Research Support Paul Ambrose, PharmD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds|Institute for Clinical Pharmacodynamics: President Pete Schmidt, MD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Myra Popejoy, PharmD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Jean Gong, PhD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds Xia Pu, PhD, Adagio Therapeutics: Employee|Adagio Therapeutics: Stocks/Bonds.